Proechimys guyannensis: An animal model of resistance to epilepsy - Arida, Ricardo Mario [UNIFESP] (2005)
Purpose: the potential interest of Proechimys guyannensis (PG), a spiny rat species living in the Amazonian region, as an animal model of anticonvulsant mechanisms, prompted the investigation of the susceptibility of this animal species to different epileptogenic treatments.Methods: Adult male Wistar and PG animals were submitted to amygdala kindling, the pilocarpine model and the intrahippocampal kainic acid (KA) model. Electrographic, behavioral, and neuropathological changes were compared between Wistar and PG animals.Results: PG animals demonstrated a striking resistance to reaching stage 5 of kindling. of the 43 PG rats submitted to the kindling process, only three animals reached stage 5. in the pilocarpine and KA models, doses lower than those used in Wistar rats were able to induce status epilepticus (SE) in PG animals. Pilocarpine-induced SE in PG had a shorter duration, rarely exceeding 2 h, in contrast to the 8- to 12- h long SE in the Wistar rat. of the 61 PG animals injected with pilocarpine, 48 presented with SE and only two presented with some spontaneous seizures after silent periods of 60 and 66 days. KA elicited self-sustained electrographic SE in PG animals, which lasted for 72 h. None of the surviving animals presented with spontaneous seizures in the long-term observation period (up to 120 days).Conclusions: These findings indicate that the PG animal may have natural endogenous anticonvulsant mechanisms and also may be an animal model that is resistant to epileptogenic treatments.